Health, dependency and caregiving: barriers to economic activity among individuals aged 50 to 69 years in Mexico - Carlos Fernando Félix-Vega; Jeroen Spijker; Pilar Zueras (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract: In Mexico, the economically active population aged over 50 years has been increasing in recent years. Due to their age, these workers may experience health deterioration and require some form of care. However, only formal employment is associated with better access to health services and pensions. At the same time, these workers may also need to care for children, sick partners or dependent older adults, which limits their time available for employment. This study examined the association between disability, receiving and providing care and access to health services, and economic activity among adults aged 50 to 69 in Mexico in 2015 and 2018. Multilevel modeling was conducted using data from the Mexican Health and Aging Study (MHAS). The MHAS is a longitudinal panel study of adults aged 50 years and older. The study sample included data from 8,831 observations from 2015 and 10,445 observations from 2018. Those living with some degree of disability and receiving care were found to be less likely to be economically active than those living with disability and not receiving care. Similarly, individuals who care for someone were also found to be less likely to be employed. Furthermore, the data suggested that individuals without access to health services were more likely to be economically active. For individuals aged 50 to 69 years, health and care issues were factors that limited economic activity status. In family-oriented societies with weak welfare states, the right to health is partial for the population and care is traditionally the responsibility of women, which exacerbates gender inequalities and has a differential impact on paid work for men and women.